2008
DOI: 10.1002/ajhb.20733
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities of somatotype components in a population from rural Mozambique

Abstract: There have been few genetic studies of normal variation in body size and composition conducted in Africa. In particular, the genetic determinants of somatotype remain to be established for an African population. (1) To estimate the heritabilities of aspects of somatotype and (2) to compare the quantitative genetic effects in an African population to those that have been assessed in European and American populations. The sample composed of 329 subjects (173 males and 156 females) aged 7-17 years, belonging to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…A Portuguese family study reported a resemblance in somatotype components within siblings, indicating the effect of familial factors but did not report heritability estimates (Pereira et al, 2017). A Canadian family study reported heritability estimates varying between 0.56 and 0.64 (Katzmarzyk et al, 2000) whereas a family study from rural Mozambique reported lower heritability estimates varying between 0.30 and 0.40 (Saranga et al, 2008); these estimates are thus substantially lower than the estimates in our study. Family studies, however, typically produce lower heritability estimates than twin studies, well shown for BMI (Elks et al, 2012), which may be because in family studies participants are typically measured at different ages when putative different genetic components may affect body composition as well as body shape.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…A Portuguese family study reported a resemblance in somatotype components within siblings, indicating the effect of familial factors but did not report heritability estimates (Pereira et al, 2017). A Canadian family study reported heritability estimates varying between 0.56 and 0.64 (Katzmarzyk et al, 2000) whereas a family study from rural Mozambique reported lower heritability estimates varying between 0.30 and 0.40 (Saranga et al, 2008); these estimates are thus substantially lower than the estimates in our study. Family studies, however, typically produce lower heritability estimates than twin studies, well shown for BMI (Elks et al, 2012), which may be because in family studies participants are typically measured at different ages when putative different genetic components may affect body composition as well as body shape.…”
Section: Discussioncontrasting
confidence: 80%
“…Meta‐analyses of previous twin studies have shown moderate heritability estimates (ie, the proportion of total variation explained by genetic variation) for aerobic physical fitness (Schutte, Nederend, Hudziak, de Geus, & Bartels, 2016) and muscle strength‐related traits (Zempo et al, 2017). For somatotype components, moderate to high heritability estimates have been found in twin studies (Peeters et al, 2003; Peeters et al, 2007; Reis et al, 2007), whereas studies using family and pedigree designs have reported moderate heritabilities and some of them have not been able to distinguish genetic factors from other familial factors (Katzmarzyk et al, 2000; Pereira et al, 2017; Rebato, Jelenkovic, & Salces, 2007; Saranga et al, 2008). Since different models with different assumptions have been used in these studies, it is difficult to compare the heritability estimates derived from them.…”
mentioning
confidence: 99%
“…Concerning anthropometric somatotype, the lowest genetic determination observed for the fatness component (endomorphy) was in the range of the previously mentioned obesity phenotypes. The lack of congruence between the published studies in defining which somatotype component is more heritable results in different patterns of heritability among the populations [19,[41][42][43].…”
Section: Discussionmentioning
confidence: 98%
“…Endomorphy is the relative fatness, mesomorphy is the relative musculo-skeletal robustness and ectomorphy is the relative linearity or slenderness (Heath & Carter, 2002). There are many factors like gender, genetics, feeding habits and environment that affect human shape and size (Saranga et al, 2008;Reis et al, 2007). Somatotype is also seen to vary with change in physical activity as well.…”
Section: Introductionmentioning
confidence: 99%